Syntheses and investigations of metal complexes with tripodal and macrocyclic ligands - Schneider, Lars; Justus Liebig University Giessen (My University, 2025)
This dissertation focuses on developing metal complexes, particularly copper complexes, for activating oxygen and/or hydrogen peroxide.
The first part focuses on the tripodal ligand imine3tren (tris(2-(propan-2-ylideneamino)-ethyl)amine), which was used to confirm the crystalline structures of various metal complexes, including zinc, nickel, sodium, and copper complexes. However, the formation of a copper-dioxygen intermediate could not be confirmed.
The second part is about the macrocyclic ligand (tBu)2(nPrSO3)Htacn, which has a higher water solubility due to its sulfonic acid group. The formation of copper dioxygen intermediates were confirmed with dioxygen in aprotic solvents and with hydrogen peroxide in protic solvents. Based on kinetic investigations, a mechanism for the formation of a copper-dioxygen intermediate in water was established.
Keywords: Metallkomplexe; Bioanorganik; Kupferkomplexe; ddc:540